Synthesis, characterization and properties of polyimides with spirobisbenzoxazole scaffold structure. (21st July 2022) - Chen, Haiquan; Dai, Fengna; Wang, Mengxia; Ke, Zhao; Yan, Kuangguo; Li, Dongwu; Chen, Chunhai; Qian, Guangtao; Yu, Youhai
Abstract: Novel diamines containing spirobisbenzoxazole scaffold structure were successfully synthesized. These diamines were homopolymerized with commercial 4, 4'-(hexafluoroisopropylidene)diphthalic anhydride (6FDA) and cyclohexanedianhydride (H'PMDA) to prepare a series of benzoxazole based polyimides (PBOIs). The obtained PBOIs exhibited good organic solubility and outstanding thermal properties, including glass transition temperature ( T g ) of 355–400 °C and 5% thermal decomposition temperatures ( T d5% ) of 474–490 °C. Meanwhile, these polymer films exhibited excellent mechanical strength, such as tensile strength of 79.4–92.1 MPa and elongation at break of 19.5%∼31.2%. In addition, such PBOIs have been proved to be novel microporous polymer with pore width distribution of 5–7 Å and BET surface area of 281–378 m 2 /g. The permeability-selectivity relationship of H'PMDA based PBOIs was close to the 2008 Robeson upper bound for CO2 /CH4 and O2 /N2 gas pairs, showing promise in the field of gas separation. Graphical abstract: Image 1 Highlights: Spirobibenzoxazole scaffold based Polyimides. Good solubility and microporosity. The permeability-selectivity relationship of H'PMDA based polyimides for CO2 /CH4 and O2 /N2 gas pairs close to the 2008 Robeson upper bound.